Analysis Of Critical Thinking Abilities Held by SMK Students Based on The Teacher's Evaluation - Mei Nanda Sari (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Students who select vocational education are expected to learn the skills required for the transition from school to the workplace. This flexibility is a crucial component of their capacity to think critically about their current situation. One of the abilities that allows a person to study things more fully, present arguments, draw conclusions, make judgements, and evaluate the repercussions of actions to be made is the ability to think critically. Critical thinking skills may be developed and taught in an educational setting. The goal of this study was to measure the amount of critical thinking abilities held by SMK students based on the teacher's evaluation. This is a descriptive study of teachers at SMK Siti Banun Rantauprapat and their understanding of network computer engineering abilities (TKJ) in 2021/2022. Giving surveys to instructors on productive, adaptive, and normative themes is one approach of gathering information on students' analytical ability. As a result of the data collected thus far, it is possible to conclude that pupils who dominate have not properly exercised their critical thinking abilities. This is because educators' capacity and competency must be enhanced and improved in order to inspire students to think critically during the learning process